2021
DOI: 10.1097/ee9.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and inflammatory effects in a Canadian pregnancy cohort

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…47 Daily mean concentrations for all ambient air pollutants were averaged to represent exposures 14 days before the collection of blood samples for CRP measurement. In our previous work, the specific 14-day exposure window had the strongest and most consistent association with CRP levels, 46 which is consistent with a previous review paper. 51…”
Section: Study Population and Designsupporting
confidence: 90%
See 1 more Smart Citation
“…47 Daily mean concentrations for all ambient air pollutants were averaged to represent exposures 14 days before the collection of blood samples for CRP measurement. In our previous work, the specific 14-day exposure window had the strongest and most consistent association with CRP levels, 46 which is consistent with a previous review paper. 51…”
Section: Study Population and Designsupporting
confidence: 90%
“…In previous investigations of this cohort, we showed that PM 2.5 exposure during late pregnancy was positively associated with CRP concentrations over 14-day and 30-day exposure windows 46 and that exposures to PM 2.5 and NO 2 during pregnancy were associated with reduced birthweight. 47 The primary objective of this study is to extend the previous work on biomarkers, by investigating the independent and combined effects of PM 2.5 , NO 2 , and O 3 , on CRP concentrations.…”
Section: Introductionmentioning
confidence: 49%
“…Studies have found that PM 2.5 can inhibit the gene expression and activity of endogenous antioxidant enzymes (48), activate the body's oxidative stress response, and promote dysfunction in multiple organs and systems (49,50). Previous studies have reported that increased traffic-related PM 2.5 concentrations are associated with altered responses to inflammatory markers (51). Animal experiments have found that artificial PM 2.5 exposure can induce increased levels of interleukin (IL)-1, IL-6 and tumor necrosis factor α (TNFα) in rats, thereby increasing the risk of nasal lesions (52).…”
Section: Discussionmentioning
confidence: 99%
“…Only limited human studies have demonstrated a link between prenatal metal exposure and an increase in maternal inflammatory markers. [45][46][47][48][49] Notably, Farzan et al 45 observed a relationship between prenatal arsenic exposure and an increase in cord blood of ICAM1 and VCAM1 in the New Hampshire Birth Cohort (n = 563). Similarly, in the present study, we observed significant positive associations between Ni and CRP and between Pb and VCAM (Table 2).…”
Section: Discussionmentioning
confidence: 99%